The BAFF/NFκB axis is crucial to interactions between sorafenib‐resistant HCC cells and cancer‐associated fibroblasts. Issue 9 (16th July 2021) - Gao, Luping; Morine, Yuji; Yamada, Shinichiro; Saito, Yu; Ikemoto, Tetsuya; Tokuda, Kazunori; Miyazaki, Katsuki; Okikawa, Shouhei; Takasu, Chie; Shimada, Mitsuo
Abstract: The tumor microenvironment affects malignancy in hepatocellular carcinoma (HCC) cells, and cancer‐associated fibroblasts (CAFs) play an important role in the microenvironment. As recent studies indicated a difference between CAFs isolated from chemoresistant and non‐resistant cancer tissues, therefore we investigated the intracellular mechanism in resistant HCC co‐cultured CAFs and interactions between these CAFs with cancer cells. We established a sorafenib‐resistant (SR) Huh7 (human HCC) cell line, and characterized it with cytokine assays, then developed CAFs by co‐culturing human hepatic stellate cells with resistant or parental Huh7 cells. The 2 types of CAFs were co‐cultured with parental Huh7 cells, thereafter the cell viability of these Huh7 cells was checked under sorafenib treatment. The SR Huh7 (Huh7 SR ) cells expressed increased B‐cell activating factor (BAFF), which promoted high expression of CAF‐specific markers in Huh7 SR ‐co‐cultured CAFs, showed activated BAFF, BAFF‐R, and downstream of the NFκB‐Nrf2 pathway, and aggravated invasion, migration, and drug resistance in co‐cultured Huh7 cells. When we knocked down BAFF expression in Huh7 SR cells, the previously increased malignancy and BAFF/NFκB axis in Huh7 SR ‐co‐cultured CAFs reversed, and enhanced chemoresistance in co‐cultured Huh7 cells returned as well. In conclusion, the BAFF / NFκB pathway was activated in CAFs co‐cultured with cell‐culture medium from resistant Huh7, which promoted chemoresistance, and increased the malignancy in co‐cultured non‐resistant Huh7 cells. This suggests that the BAFF/NFκB axis in CAFs might be a potential therapeutic target in chemoresistance of HCC. Abstract : In this study, we established a sorafenib‐resistant (SR) Huh7 (human hepatocellular carcinoma [HCC]) cell line, and developed cancer‐associated fibroblasts (CAFs) induced from resistant or parental Huh7 cells. We found that the B‐cell activating factor (BAFF)‐NF κ B pathway was activated in sorafenib‐resistant Huh7‐co‐cultured CAFs, which promoted chemoresistance and increased malignancy in co‐cultured non‐resistant Huh7 cells. This suggests that the BAFF‐NF κ B axis plays a crucial role between the interaction of SR HCC and CAFs, and it might be a potential therapeutic target in CAFs that caused chemoresistance of HCC.